Value of Microimmunofluorescence for Diagnosis and Follow-up of Bartonella Endocarditis - Fournier, Pierre-Edouard (American Society for Microbiology, 2002)
Bartonella endocarditis is a disease of emerging importance that causes serious complications and high rates of mortality. Due to the fastidious nature of Bartonella species and their high degrees of antibiotic susceptibility, cultures of clinical samples most often remain sterile and valvular biopsy specimens, the best specimens for PCR amplification, are seldom available. Therefore, serology appears to be the easiest diagnostic tool. In order to determine the best cutoff value for serology and its predictive values for the detection of Bartonella endocarditis, we studied 48 patients with culture- and/or PCR-confirmed Bartonella endocarditis. We also applied these serological criteria to 156 patients with blood culture-negative endocarditis. Furthermore, we compared the kinetics of the antibody responses to Bartonella spp. in order to estimate the value of serology for prediction of the occurrence of relapses. A titer of ≥1:800 for immunoglobulin G antibodies to either Bartonella henselae or B. quintana has a positive predictive value of 0.810 for the detection of chronic Bartonella infections in the general population and a value of 0.955 for the detection of Bartonella infections among patients with endocarditis. When this cutoff was applied to 156 patients with blood culture-negative endocarditis, we were able to diagnose Bartonella infections in an additional 45 patients with definite endocarditis for whom a positive Bartonella serology was the only evidence of infection. On follow-up, the kinetics of the decrease in antibody titers were significantly delayed in two patients with relapses. In conclusion, we recommend the determination of antibodies to both B. quintana and B. henselae and the use of a cutoff value of 1:800 for the diagnosis of Bartonella endocarditis. We propose that this criterion, which may also help with the detection of late relapses, be included as a major criterion in the Duke criteria for the diagnosis of infective endocarditis.